Preliminary Investigation of the Use of the Andong Plant in the Local Community - Secillia Putri M A Sihombing; Hapukh, Rahel Karen; Situmeang, Dia Tabitha; Putri, Najwa Alya; Samosir, Erikson (Indonesian Journal of Medical Anthropology, 2025)
This study explores the cultural and spiritual significance of Cordyline fruticosa (andong) as a sacred plant in North Sumatra. Fieldwork was conducted in four separate sites, involving community leaders, elders, younger generations, and individuals with direct experiences of spiritual or healing practices using andong. Data were collected through in-depth interviews to examine (1) local beliefs in the plant’s spiritual power, (2) its use in warding off negative forces, (3) its role in traditional rituals and healing, and (4) changes in perception and practice over time. Findings reveal the multifaceted role of andong: beyond its aesthetic and medicinal value, it serves as a medium of spiritual protection and remains central to customary ceremonies. These insights highlight andong’s enduring place in local wisdom and its relevance to ethnobotanical and medical anthropological studies.